(untitled) (Journal of Kathmandu Medical College, 2014)
Background: Smoking accounts for 8.8% of annual deaths worldwide. It is practiced by about a third of world population aged 15 years or older. About 73% of these smokers are in developing countries with overall prevalence in Nepal ranging from 25% to 73% in adult men. Objectives: To assess the prevalence of smoking among the male population, identify the perceived health problems, association between smoking status and selected variables and association between smoking status and existing health problems among respondents. Methods: A descriptive cross-sectional study was conducted using systematic random sampling among male population of Dharan municipality. The sample size was 180. Results: This study revealed that the prevalence of smoking was 41.7%. Sixty eight percentage of the respondents had started smoking at the age of 11 to 20 years and most of them initiated smoking due to peer pressure. Forty three percentage of former smokers and 52% of current smokers had experienced different kinds of health problems like cough and troubled breathing which they perceived as smoking related. A total of 64% of former smokers had quitted smoking due to health problems. Respondents with low educational status were more smokers (p<0.05), those who were unemployed and if employed then unskilled/semi skilled workers were more smokers (p<0.01). Current smokers experienced more health problems like cough and troubled breathing than non smokers (p<0.01). Conclusion: This study shows that young people are more vulnerable to start cigarette smoking so there should be frequent positive reinforcement of antismoking campaign focusing more on youth and as well the smoking advertisements should be discouraged. Journal of Kathmandu Medical College Vol. 2, No. 3, Issue 5, Jul.-Sep., 2013 Page: 129-138 DOI: http://dx.doi.org/10.3126/jkmc.v2i3.9963 Uploaded date : 3/4/2014